2019
DOI: 10.1021/acs.iecr.9b05191
|View full text |Cite
|
Sign up to set email alerts
|

HCHO Removal by MnO2(x)–CeO2: Influence of the Synergistic Effect on the Catalytic Activity

Abstract: The catalytic performance of MnO 2 (x)−CeO 2 (x = Mn/Ce molar ratio) and the synergistic effect have been investigated in formaldehyde removal. The results showed that formaldehyde achieved 100% conversion at 60 °C for MnO 2 (1.5)−CeO 2 , with the gas hourly space velocity = 120 000 mL h −1 g cat −1. It was lower than the formaldehyde removal temperature of MnO 2 (130 °C) and CeO 2 (170 °C). The apparent activation energy for HCHO oxidation with MnO 2 (1.5)−CeO 2 was 34.2 kJ mol −1 . The partial mutual replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The proportion of surface activity oxygen is summarized in Table . Obviously, Co 3 O 4 addition resulted in a significantly higher concentration of O sur species than that of the Au/CeO 2 -500 °C sample, which was consistent with the Ce 3d spectral analysis; that is, more oxygen vacancies exposed more insufficiently coordinated Ce atoms to adsorb oxygen and provided delocalized electrons to the surface-adsorbed oxygen molecules to activate them, thereby significantly increasing the content of O sur …”
Section: Resultssupporting
confidence: 78%
“…The proportion of surface activity oxygen is summarized in Table . Obviously, Co 3 O 4 addition resulted in a significantly higher concentration of O sur species than that of the Au/CeO 2 -500 °C sample, which was consistent with the Ce 3d spectral analysis; that is, more oxygen vacancies exposed more insufficiently coordinated Ce atoms to adsorb oxygen and provided delocalized electrons to the surface-adsorbed oxygen molecules to activate them, thereby significantly increasing the content of O sur …”
Section: Resultssupporting
confidence: 78%
“…The as‐constructed MnO 2 NW–CeO 2 NP binary heterostructures have been applied to the catalytic reduction of NO x , showing excellent performances and making them suitable for a wide working temperature range from 100 to 400 °C. Other MnO 2 /CeO 2 binary heterojunctions for environmental purification have also been reported by researchers, including MnO 2 /CeO 2 –MnO 2 nanocomposites for elemental mercury removal, [ 202 ] MnO 2 /CeO 2 for the catalytic degradation of methyl orange with the assistance of ultrasound, [ 203–205 ] δ‐MnO 2 /CeO 2 for toluene [ 206 ] and formaldehyde [ 207 ] catalytic combustions, MnO 2 /CeO 2 core–shell structures for the catalytic oxidation of CO [ 208 ] and catalytic reduction of NO x , [ 209,210 ] and trepang‐like MnO 2 /CeO 2 for soot removal. [ 211 ]…”
Section: Fabrication Of Mno2‐based Compositesmentioning
confidence: 99%
“…Qu et al 21 synthesized 3D Au-Ce x Co y /GA catalysts that possessed 100% HCHO removal activity at 60 °C. This is because the synergistic effect on CeO 2 and metal oxide supports enormously promoted the activation and metastasis of molecular oxygen, and Guan et al 22 also reported such a promotion mechanism.…”
Section: Introductionmentioning
confidence: 99%